The Effects of North Atlantic Oscillation on the atmospheric middle level Anomaly and precipitation of Iran.Case study: west of Iran. - Meysam Toulabi Nejad; ZAHRA Hejazizadeh; Atefeh Bosak; nasrin bazmi (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study was to investigate the effects of the North Atlantic Oscillation on the middle levels of Atmosphere and precipitation changes in the West of country. To do this, first monthly rainfall data of 17 synoptic stations of the West Country in period of 30 years from 1984 to 2014 of country were collected from Meteorological Organization. As well as North Atlantic Oscillation data and anomalies geopotential height data, sea level pressure and precipitation were received from NOAA. To clarify the relationship between the NAO index phase with precipitation of west of Iran used Pearson correlation coefficient was at least 95%, (P_value = 0.05). Finally, using synoptic maps, spatial relationships among data, were analyzed. The results indicate that between North Atlantic Oscillation changes with middle level height anomalies of the Atmosphere and the amount of precipitation in West of Iran in January, March, April and November there is communication and concurrency.  The results showed that , at a time of sovereignty positive phase of the North Atlantic oscillation , an average of height atmospheric middle level in mid - western Iran 17 meters long - term and less than the average rainfall per month 23.5 mm increased and wetly sovereign. But when phase of governance is negative, high atmospheric middle level anomaly to an average of 20 meters more than normal. As a result, the drought will prevail in the west and precipitation in the region each month will face a reduction of 30 mm. In general, we can say that droughts more severe than wet coincide with the negative phase of the North Atlantic Oscillation is positive phase.